Asymptotic normalization coefficients for 11B + p → 12C from the 11B(10B, 9Be)12C reaction and the 11B(p, γ)12C astrophysical S-factor - S.K. Sakhiyev; S.V. Artemov; N. Burtebayev; S.B. Sakuta; S.B. Igamov; Maulen Nassurlla; K. Rusek; M. Wolińska-Cichocka; N. Amangeldi; Marzhan Nassurlla; A. Trzcińska; G. Yergaliuly; et al. (Results in Physics, 2024)
The 11B(10B,9Be)12C reaction was studied at the energy of 41.3 MeV with transitions to the ground (0+) and low-lying excited 4.44 MeV (2+) and 9.64 MeV (3−) states of 12C nucleus. The analysis of the measured angular distributions was carried out using a modified distorted wave (MDWBA) method, assuming a one-step proton transfer mechanism. It was shown that at small angles (in the region of the main diffraction maximum) this reaction occurs on the nuclear surface with the dominance of a one-step process. This made possible to determine the values of asymptotic normalization coefficients (ANC) for 11B + p → 12C. The squared ANCs equal to 322 ± 76 fm−1, 32.8 ± 8.4 fm−1 and 1.26 ± 0.44 fm−1 for 0+, 2+ and 3− states of the 12C nucleus respectively were obtained. These values were used to take into account the contribution of the direct process in the calculation of astrophysical S-factors for the radiative capture of a proton by the 11B nucleus at astrophysical energies.